A study on the factors that contribute to the incompetence of making payment to vendor / Noor Zuliana Mohd Fuzi - Mohd Fuzi, Noor Zuliana (Faculty of Business and Management, 2009)
This study provides an analysis regarding to the factors that contribute to the incompetence of making payment to vendor. The purpose of this study is to determine the factors that contribute incompetence of making payment to vendor and compose some recommendations for Sapura Global Group of Companies so that the companies will be able to make timely and accurate payment to all their vendors. In Sapura Global Group Of Companies, timely and accurate payment is important because it show how efficient does Business Controller is handling Sapura cash flow. In addition, to understand what is the factors that difficult to resolve in order to make accurate payment in this company. These studies also try to answer what are the effects that may arise in the delayed the payment. In order to analyze the issues, the data that have been use to collect the data are from primary and secondary sources.